Cultural Differences in Expressed Emotion - Domínguez-Mártínez, Tecelli; Medina-Pradas, Cristina (Taylor and Francis, 2022)
The first to synthesize the exponentially growing research on expressed emotion (EE) and eating disorders and apply it to treatment, interventions, and other scenarios, this unique text provides unprecedented guidance to students, clinicians, and researchers in the field of eating disorders. This book explores the components of relatives’ attitudes and behaviors toward an ill family member and discusses a modifiable treatment target that could improve outcomes for patients through interventions, treatment plans, and future directions in research. Chapters bring together contributions from eminent scientists and clinicians in the fields of families, eating disorders, and treatment to contribute to the clinical and scholarly understanding of expressed emotion and eating disorders. Mental health professionals studying and treating eating disorders will find this text to be a valuable reference guide and will be inspired to further explore this rich and promising area of study.
Es un capítulo del libro: Rienecke, R.D., & Le Grange, D. (Eds.). (2020). Eating Disorders and Expressed Emotion: Integrating Treatment, Intervention, and a Positive Family Environment (1st ed.). Routledge.
Keywords: eating disorders; emotion; Scopus(2)